A Chemically Soldered Polyoxometalate Single‐Molecule Transistor. (12th May 2020) - Wu, Chuanli; Qiao, Xiaohang; Robertson, Craig M.; Higgins, Simon J.; Cai, Chenxin; Nichols, Richard J.; Vezzoli, Andrea
Abstract: Polyoxometalates have been proposed in the literature as nanoelectronic components, where they could offer key advantages with their structural versatility and rich electrochemistry. Apart from a few studies on their ensemble behaviour (as monolayers or thin films), this potential remains largely unexplored. We synthesised a pyridyl‐capped Anderson–Evans polyoxometalate and used it to fabricate single‐molecule junctions, using the organic termini to chemically "solder" a single cluster to two nanoelectrodes. Operating the device in an electrochemical environment allowed us to probe charge transport through different oxidation states of the polyoxometalate, and we report here an efficient three‐state transistor behaviour. Conductance data fits a quantum tunnelling mechanism with different charge‐transport probabilities through different charge states. Our results show the promise of polyoxometalates in nanoelectronics and give an insight on their single‐entity electrochemical behaviour. Abstract : An Anderson–Evans polyoxometalate functionalised with 4‐pyridyl termini has been used to fabricate single‐entity junctions in an electrochemical environment. As the charge state of the polyoxomolybdate is changed by the electrochemical potential, the fabricated devices show a tunnelling transistor behaviour, with OFF‐ON‐OFF conductance gating by more than one order of magnitude.